An Application of Machine Learning Techniques to Analyze Patient Information to Improve Oral Health Outcomes - Ameli, Nazila; Gibson, Monica Prasad; Khanna, Amreesh; Howey, Madison; Lai, Hollis (Frontiers in Dental Medicine, 2022)
Objective: Various health-related fields have applied Machine learning (ML) techniques such as text mining, topic modelling (TM), and artificial neural networks (ANN) to automate tasks otherwise completed by humans to enhance patient care. However, research in dentistry on the integration of these techniques into the clinic arena has yet to exist. The purpose of this study was to: introduce a method of reviewing patient chart information using ML, provide a step-by-step description of how it was conducted, and demonstrate this method’s potential to identify important oral health-related contributors. Methods: A secondary data analysis was conducted to demonstrate the approach on a set of anonymized patient charts collected from a dental clinic. Two ML applications for patient chart review were demonstrated: 1) text mining and Latent Dirichlet Allocation (LDA) were used to preprocess, model, and cluster data in a narrative format and extract common topics for further analysis, 2) Ordinal logistic regression (OLR) and ANN were used to determine predictive relationships between the extracted patient chart data topics and oral health-related contributors. All analysis was conducted in R and SPSS (IBM, SPSS, statistics 22). Results: Data from 785 patient charts were analyzed. Preprocessing of raw data (data cleaning and categorizing) identified 66 variables, of which 45 were included for analysis. Using LDA, 10 radiographic findings topics and 8 treatment planning topics were extracted from the data. OLR showed that caries risk, occlusal risk, biomechanical risk, gingival recession, periodontitis, gingivitis, assisted mouth opening and muscle tenderness were highly predictable using the extracted radiographic and treatment planning topics and chart information. Using the statistically significant predictors obtained from OLR, ANN analysis showed that the model can correctly predict greater than 72% of all variables except for bruxism and tooth crowding (63.1% and 68.9%, respectively). Conclusion: Our study presents a novel approach to address the need for data-enabled innovations in the field of dentistry and creates new areas of research in dental analytics. Utilizing ML methods and its application in dental practice has the potential to improve clinicians’ and patients’ understanding of the major factors that contribute to oral health diseases/conditions.